Valorising University Education in Ghana - Amo-Agyemang, C. (International Journal of African Renaissance Studies - Multi-, Inter- and Transdisciplinarity, 2019)
There has been a neoliberal re-ordering of the political intent behind education in Ghana. Prior to the said re-ordering, education was a means by which the government facilitated the citizen’s acquisition of the social capital required to enable the individual to contribute to the positive development of the state. The state intervened to create a common sense of nationhood and destiny among the citizenry in the quest for national reconstruction. However, the neoliberal “commodification” of education—in the form of a philosophical readjustment of the need for education, from being a “right” to a “privilege”—and its attendant shifting of the cost onto the citizen, have led to the creation of segregation based on income. The poor have thus been permanently locked out of education as a means of upward social mobility. The result of this is socio economic disharmony, with the educational system as a political filter which separates those who can afford education and those who cannot. This has negative implications for the process of democratic deepening: the educationally empowered will lord it over the educationally disempowered. Stretched to its logical conclusion, the state, even though liberal, becomes an oppressive democratic state, with structurally limited options for the poor.
Research Article
Keywords: neoliberalism; Ghana; university; free market; Foucault; academe